2019
DOI: 10.5435/jaaos-d-17-00811
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresented Minority Applicants Are Competitive for Orthopaedic Surgery Residency Programs, but Enter Residency at Lower Rates

Abstract: Introduction: Orthopaedic surgery residency programs have the lowest representation of ethnic/racial minorities compared with other specialties. This study compared orthopaedic residency enrollment rates and academic metrics of applicants and matriculated residents by race/ethnicity. Methods: Data on applicants from US medical schools for orthopaedic residency and residents were analyzed from 2005 to 2014 and compared between race/ethnic groups (White, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 9 publications
3
71
1
Order By: Relevance
“…These studies show that a heavy emphasis on USMLE Step 1 in orthopaedic surgery is more likely to select students from higher socioeconomic backgrounds who happen to be English-speaking Caucasian men. Poon et al found that between 2005 and 2014, URM applicants to orthopaedic surgery had greater numbers of volunteer experiences and publications, whereas Caucasian and Asian applicants had higher USMLE Step scores and AOA statuses 23 . If the latter application items are playing a larger role in screening applicants, it is unlikely that a residency will significantly change the ethnic/racial composition of their residents.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that a heavy emphasis on USMLE Step 1 in orthopaedic surgery is more likely to select students from higher socioeconomic backgrounds who happen to be English-speaking Caucasian men. Poon et al found that between 2005 and 2014, URM applicants to orthopaedic surgery had greater numbers of volunteer experiences and publications, whereas Caucasian and Asian applicants had higher USMLE Step scores and AOA statuses 23 . If the latter application items are playing a larger role in screening applicants, it is unlikely that a residency will significantly change the ethnic/racial composition of their residents.…”
Section: Discussionmentioning
confidence: 99%
“…In other health care professions, such as orthopedic surgical residencies, URM applicants are enrolled at a lower rate than non-URM applicants, which may deter URM applicants, limit URM exposure to the field, and inhibit interaction with potential mentors. 33,34 More research must be done, and data must be shared by professional organizations like American Society of Health-System Pharmacy, to better understand URM interests and matching to residencies.…”
Section: Discussionmentioning
confidence: 99%
“…43 Career goals are thought to be influenced through the process of development and determined by two types of factors: 1) intrinsic factors, such as personal interest and 2) extrinsic factors, such as salary and cost of training. 33 Participants in this study selected job security as a key factor in career goals, which is related to both intrinsic and extrinsic motivators for work. 45 In addition, self-actualization was frequently selected as important career selection.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Poon et al. 5 showed that Orthopedic residency applicants who were White were more likely to get accepted despite Hispanic students having more publications and Black applicants having more volunteer hours. Bias - conscious or unconscious - was not investigated, but it is well known to be a factor that affects those UIM.…”
mentioning
confidence: 99%